2002
DOI: 10.1016/s0304-3959(02)00261-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high and low frequency electroacupuncture in pain after lower abdominal surgery

Abstract: In the present study, we examined the effects of preoperative electroacupuncture (EA) at classical bilateral acupuncture points (Zusanli, also known as ST-36) on postoperative pain and opioid-related side effects. One hundred healthy consenting women undergoing lower abdominal surgery were randomly assigned to four treatment regimens: Group I (n=25), control; Group II (n=25), sham-EA (needle insertion without electrical stimulation); Group III (n=25), low-EA (2 Hz of electrical stimulation); and Group IV (n=25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
136
1
13

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(162 citation statements)
references
References 41 publications
12
136
1
13
Order By: Relevance
“…Acupuncture and low and high frequency EA decreased the total amount of morphine by 21, 43 and 61%, respectively during the first postoperative 24 h following lower abdominal surgery (LIN et al, 2002) and AP reduced consumption of supplemental IV morphine by 50% for four days after lower and upper abdominal surgery (KOTANI et al, 2001). In the present study, 12.5% of the animals required morphine to complement analgesia, compared to 62.5% in the CG, within 5 hours following surgery.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Acupuncture and low and high frequency EA decreased the total amount of morphine by 21, 43 and 61%, respectively during the first postoperative 24 h following lower abdominal surgery (LIN et al, 2002) and AP reduced consumption of supplemental IV morphine by 50% for four days after lower and upper abdominal surgery (KOTANI et al, 2001). In the present study, 12.5% of the animals required morphine to complement analgesia, compared to 62.5% in the CG, within 5 hours following surgery.…”
Section: Discussionsupporting
confidence: 44%
“…Abdominal surgery have been successfully performed under AP analgesia in dogs (LOPES et al, 1998;STILL, 1987;WRIGHT;MCGRATH, 1981), but this technique has more frequently been used to treat postoperative pain in dogs and humans (DI MARTINO;LIN et al, 2002;PIGNATON et al, 2007;SOUSA et al, 2012;TEIXEIRA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that sham-EA exerts a beneficial effect with respect to its pain relieving quality but not on the side effect profiles. Our findings demonstrate that preoperative treatment with lowand high-EA can reduce postoperative analgesic requirements and associated side effects in patients undergoing lower abdominal surgery (Lin, et al, 2002).…”
Section: Effect Of High and Low Frequency Ea On Pain After Lower Abdomentioning
confidence: 57%
“…[12][13][14][15] Evidence suggests that acupuncture activates C-afferent fibers and A-d fibers, altering transmission of pain signals at the spinal cord, midbrain, and hypothalamus. Stimulation of A-d and C-afferent fibers in the muscle depresses nociception in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%